Dietary Content and Type of Lipids and Selenium Supplement on Fatty Acid Profile in Meagre (Argyrosomus regius) - Tiago Simões; Sthelio Fonseca; Sthelio Fonseca; Rodrigo Ozorio; Rodrigo Ozorio (Frontiers in Marine Science, 2014)
Global aquaculture production has increased drastically since mid-1970s, playing an important role as a source for high-protein and essential dietary lipids. Within the new-farmed fish species, meagre (Argyrosomus regius) is a suitable candidate species for the diversification of aquaculture. This species has revealed great potential as a farming species, due to its excellent biological characteristics and relatively high growth rates, high efficiency in utilize dietary nutrients and high fertility. In addition, meagre has good marketing potential and can be processed into portions (fillets, loins) to supply the growing segment for portion sized ready-to-cook products, provided commercial size is attained (>2 kg). This study aimed to evaluate lipid level and essential fatty acids incorporation into farmed meagre tissues through the administration of 8 isoproteic diets with varying lipid levels (12 and 17%) consisting of different oil sources (marine fish oil (FO), rich in Oleic, ARA, EPA and DHA and a vegetable oil mix (VO), rich in Oleic, Linoleic and α-Linolenic acids) and two levels of dietary selenium (0.0 and 1.0 mg kg-1) in a 2 × 2 × 2 factorial design. Fish were distributed into 24 glass-fibre tanks of 80L each and fed in triplicate (3 tanks/treatment, 25 fish/tank) for 90 days. Rearing conditions (temp.: 20.7 ± 0.7 ºC, O2: 8.8 ± 1.7 mg L-1, 12h:12h photoperiod) were daily monitored. During the feeding trial, muscle and liver samples from all eight treatments were excised at 60 days for the determination of total lipids and fatty acids profiles. Fish fed with FO diets have better feed conversion (1.69 ± 0.17 vs. 2.26 ± 0.44), weight gain (13.09 ± 1.59 g vs. 9,97 ± 1.68g) and specific growth rate (0.84 ±0.13 vs. 0.65 ± 0.10) then those fed with vegetable oil. Diets with 12% lipid showed significant differences in weight gain (12.30g to 10.76g) and specific growth rate (0.80 to 0.69) compared with 17% lipid diets. No effects were observed for selenium levels in growth performance of meagre. Total lipid content and several fatty acid profiles changed in both tissues with the dietary lipid source (Tables 1 and 2). Total lipid content in muscle tissue increased with the FO diet, comparatively to the VO diet (6.11 to 7.04%). In liver tissue, it increased abruptly with VO diet (31.59 to 51.73%). The selenium addition in the diets might also be linked to lipid content, as in fatty acid profile. Total muscle tissue lipids supplemented with selenium and VO increased 0.36% in average and total liver lipids increased 6.94% in average. The FO diet supplemented with selenium affects mostly the liver, by reducing the total lipid content. The increment of total lipids in this diet (12% to 17%) also elevates total lipid content in liver 3.14%, in average. The disparity in the fatty acid profile in the specimens fed with different diets reveal elevated rates of fatty acid incorporation in their tissues. EPA (C 20:5) and DHA (C 22:6) fatty acids are more present in the tissues with the fish oil diet. DHA concentrates more in the muscle (16.25% and 8.94%) than in the liver (5.55% and 0.30%) (Table 2). Oleic (C 18:1), linoleic (C 18:2) and α-linolenic (C 18:3) fatty acids are more expressive in the animals supplemented with vegetal oil, being Oleic acid the most accumulated in the liver (40.99%).